Cinco de Mayo - Riehecky, Janet, 1935-; Stasiak, Krystyna (Chicago : Childrens Press, 1993)
Although Maria is not too successful at helping her family prepare for Cinco de Mayo, she wins an art contest at the library and gets to break the pinata back home. Includes instructions for making tacos and three crafts.
Book Links (A.L.A.).
Booklist.
School Library Journal.
2.7
K-3
Keywords: Cinco de Mayo (Mexican holiday) -- Fiction; Cinco de Mayo (Mexican holiday) -- Fiction